Problems of western discount rate calculation models application in the process of Russian companies business valuation - A. A. Myskin (Путеводитель предпринимателя, 2020)
Discount rate calculation is one of the most important stages of valuation process. This research provides description of discount rate economic substance, analysis of Russian business institutional environment and stock market which lead to problems of application of western discount rate calculation models. In conclusion the advantages and disadvantages of using Russian stock market data are stated.